A nanoscaled Au–horseradish peroxidase composite fabricated by an interface reaction and its characterization, immobilization and biosensing. Issue 8 (24th March 2015) - Liu, Suli; Wei, Tianxiang; Liu, Qian; Tu, Wenwen; Lan, Yaqian; Han, Min; Bao, Jianchun; Dai, Zhihui
Abstract : We develop a novel strategy for the biosensing application of hydrogen peroxide (H2 O2 ) using a nanoscaled Au–horseradish peroxidase (HRP) composite thin film synthesized by a liquid–liquid interface reaction. Abstract : We develop a novel strategy for the biosensing application of hydrogen peroxide (H2 O2 ) using nanoscaled Au–horseradish peroxidase (HRP) composite thin film synthesized by a liquid–liquid interface reaction. Through the interaction between Au nanoparticles and NH2 -terminated HRP, HRP is effectively combined with Au in the thin film. The nanocomposite membrane is extracted on the surface of the ITO electrode directly, retaining its bioactivity during the immobilization process, which can detect the substrate in situ . The immobilized HRP displays an excellent electrocatalytic response to the reduction of H2 O2, with a fast amperometric response (within 5 s), wide linear range (7.9 μM to 3.6 mM), low detection limit (0.035 μM), and a good affinity ( K appm = 0.14 mM) to H2 O2 . The prepared biosensor also exhibits high sensitivity, good reproducibility and long-term stability. Furthermore, it can be successfully exploited for the determination of H2 O2 released from living cells directly adhered on the modified electrode surface.